2021
DOI: 10.29333/iji.2021.14239a
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female University Students’ Perceptions of an Effective EFL Teacher

Abstract: Examining and understanding the concept of effective language instruction is of major significance as regards the process of teaching and learning foreign languages. This study attempts to investigate the differences in the male and female EFL (English as a foreign language) students' perceptions of effective language teachers. The convenient sampling technique, followed by the stratified sampling, was applied to gather the data from 25 males and 58 females (n=83). First, ten highest-mean and ten lowest-mean i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…However, that item was included in the bottom 10 for students and teachers in our study, which agrees with female Slovakian students (Metruk, 2021). Moreover, students and teachers in the literature stated the importance of varied classroom activities (Al-Mahrooqi et al, 2015;Brosh, 1996;Chen, 2012;Metruk, 2021). However, it was only teachers in this study who included this item in the top 10.…”
Section: Pedagogical Knowledge About Learning and Teachingsupporting
confidence: 84%
See 2 more Smart Citations
“…However, that item was included in the bottom 10 for students and teachers in our study, which agrees with female Slovakian students (Metruk, 2021). Moreover, students and teachers in the literature stated the importance of varied classroom activities (Al-Mahrooqi et al, 2015;Brosh, 1996;Chen, 2012;Metruk, 2021). However, it was only teachers in this study who included this item in the top 10.…”
Section: Pedagogical Knowledge About Learning and Teachingsupporting
confidence: 84%
“…Omani students stated that knowledge of current trends in English language teaching was a requirement for an effective English language teacher. However, that item was included in the bottom 10 for students and teachers in our study, which agrees with female Slovakian students (Metruk, 2021). Moreover, students and teachers in the literature stated the importance of varied classroom activities (Al-Mahrooqi et al, 2015;Brosh, 1996;Chen, 2012;Metruk, 2021).…”
Section: Pedagogical Knowledge About Learning and Teachingsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the results showed that experienced EFL teachers focused on studentcentred teaching, which was pertinent to their beliefs about foreign language teaching and learning. They designed diversified teaching content and employed teaching strategies to meet students' different needs and interests [11,15,54,61]. They simultaneously considered different cultural settings [54] and assessed prior teaching and learning experience.…”
Section: Profile Of Efl Teachers' Professional Qualitymentioning
confidence: 99%
“…As an important agenda, language teacher professional quality has gained in popularity in LTE research [8][9][10], particularly along with some updated teaching methods including communicative language teaching (CLT), and more recently task-based language teaching (TBLT) and content and language integrated learning (CLIL). Some scholars have paid special attention to the quality of expert or effective EFL teachers [10][11][12][13][14][15]. Research into teacher excellence has been conducted to interpret and improve their professional experiences and beliefs [16], thus providing an effective reference for more inexperienced teachers [17], especially those working in underprivileged rural areas.…”
Section: Introductionmentioning
confidence: 99%